If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -67 + -13p = 150 + -11 Reorder the terms: -67 + p + -13p = 150 + -11 Combine like terms: p + -13p = -12p -67 + -12p = 150 + -11 Combine like terms: 150 + -11 = 139 -67 + -12p = 139 Solving -67 + -12p = 139 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '67' to each side of the equation. -67 + 67 + -12p = 139 + 67 Combine like terms: -67 + 67 = 0 0 + -12p = 139 + 67 -12p = 139 + 67 Combine like terms: 139 + 67 = 206 -12p = 206 Divide each side by '-12'. p = -17.16666667 Simplifying p = -17.16666667
| -2(4x+2)=-8x+2 | | 12=-5x-8 | | 2(2x+7)=17 | | 2x^2-28x+83=0 | | 20=(8w+7/4)+(w-7/8) | | Z/8+3/4=6+z/2 | | 50-2x=16 | | 3/m+7=5/-8 | | 6x+3+2x+4=79 | | -4x-8=3x-71 | | 3/4(x+4)=-4x | | 6p^3+10p^3= | | 2(2x+8)=3x+32 | | 1/3(x-9)=2x+7 | | 3x+4x-2=61 | | 6(-3-x)2x=14 | | 7x-2(3+4x)=1 | | (ax-by)(ax-by)+11(ax-by)-60=0 | | -3x+52=7x+12 | | -a+4=2 | | 5p^4+7p^4= | | 1/4=a/2-1/8 | | 17+n=n+28 | | 5x-15-8=-33 | | 1b+2c+5g=8t | | (ax-by)(ax-by)+11(ax-by)-60=(ax-by+15)(ax-by-4) | | 14x=7(2x+2) | | 9+6+4x=64 | | 0.08(y-6)+0.14y=0.10y-0.9 | | 4k+9l+9/5 | | 6(x+2)+2x=36 | | 63=19x-32 |